Electrocardiographic Comparison of Ventricular Premature Complexes during Exercise Test in Patients with CPVT and Healthy Subjects. - Blich, Miry; Marai, Ibrahim; Suleiman, Mahmoud; Lorber, Avraham; Gepstein, Lior; Boulous, Monther; Khoury, Asaad (Pacing & Clinical Electrophysiology, 2015)
Background Catecholaminergic polymorphic ventricular tachycardia (CPVT) is a rare but highly malignant inherited arrhythmic disorder. Although a standardized exercise stress test (ST) is the most reliable way to diagnose CPVT, in 30% only single ventricular premature beats (VPCs) were recorded. Objective To evaluate whether electrocardiographic characteristics of VPCs during ST distinguish patients with CPVT from healthy subjects. Methods Electrocardiographic characteristics of VPCs during ST in 16 calsequestrin-2 (CASQ2) mutation carriers CPVT patients were compared with that in 36 healthy subjects. Results CPVT patients had more VPCs (31 ± 14 vs 3 ± 4, P < 0.0001), longer QRS duration (139 ± 18 ms vs 121 ± 21, P = 0.004), and coupling interval (CI; 476 ± 58 ms vs 355 ± 61 ms, P < 0.0001). The most sensitive characteristics for CPVT were >10 VPCs/test (100% sensitivity, 100% negative predictive value [NPV]), left bundle branch block (LBBB) pattern with inferior axis (88% sensitivity, 94% NPV), and CI longer than 400 ms (88% sensitivity, 94% NPV). Bigeminy or trigeminy or LBBB pattern with inferior axis was most specific for CPVT at 100% (100% positive predictive value PPV, 92% NPV). First VPC during the recovery period and VPC recording more than 1 minute during the recovery period were most specific for healthy subjects (100% specificity, 100% PPV). In multivariate analysis, QRS duration >120 ms (odds ratio 4.2, 95% confidence interval 1-17.6, P = 0.04) and first VPC at ≥10 mets (odds ratio 9.1, 95% confidence interval 2.01-41.1, P = 0.004) each predicted the presence of CPVT. Conclusions Several electrocardiographic criteria can help distinguish VPCs originating from CPVT compared with healthy subjects.